Influence of the boronizing treatment on Fe-Mn-Al-Si-C steel - Casteletti, Luiz Carlos; Takeya, Gustavo Satoru; Neto, Amadeu Lombardi; Picon, Carlos Alberto [UNESP]; Totten, George Edward (My University, 2015)
Austenitic Fe-Mn-Al-Si-C steel provides excellent cold formability and lower density compared to conventional stainless steels. These steels owe their corrosion and oxidation resistance to their aluminum and silicon contents, and the stability of their gamma phase is due to manganese and carbon alloying elements. The production of a boride layer with high hardness can significantly increase its surface hardness and consequently its wear resistance. In this work, Fe-31Mn-7.5Al-1.3Si-0.9C steel samples were subjected to a boriding treatment for 4 hours at 900°C. The composition of the bath was 90% borax and 10% aluminum. Boride layers with high hardness levels were obtained (1900 HV). There was also a marked increase in wear resistance of the material.
Keywords: Austenitic Fe-Mn-Al-Si-C steel; Boronizing; Corrosion; Wear